MENELISIK FENOMENA NIKAH SIRRI (Sebuah Kajian Tematik dalam Komunikasi Islam) - Pardianto Pardianto (DIALEKTIKA, 2019)
ABSTRACT Sirri marriage phenomenon recently began to become news and conversations throughout the media, both electronic media (television, internet / medsos) and print media (newspapers and magazines). In the site was also explained, that sirri marriage program is an online siri marriage application that can be accessed through android applications. The goal is to help meet someone with prospective bride dreams quickly and accurately. The purpose of this writing is how to marry sirri according to Islam and the state and how the communication of Islam mengelisik marriage phenomenon sirri. The results of the analysis prove that the law of marriage betel by rule of religion is legitimate. And permitted or allowed if laden and rukun nika are met. But legally applicable in our country on marriage legislation is not valid because in the legislation there are not complete administratively. The greatest amount of marriage siri affects the women and children for their future. Keywords: Sirri Marriage